Development of a Highly Efficient Multiplex Genome Editing System in Outcrossing Tetraploid Alfalfa (Medicago sativa) - Wolabu, Tezera W.; Cong, Lili; Park, Jong-Jin; Bao, Qinyan; Chen, Miao; Sun, Juan; Xu, Bin; Ge, Yaxin; Chai, Maofeng; Liu, Zhipeng; Wang, Zeng-Yu (Frontiers in Plant Science, 2020)
Alfalfa (Medicago sativa) is an outcrossing tetraploid legume species widely cultivated in the world. The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (CRISPR/Cas9) system has been successfully used for genome editing in many plant species. However, the use of CRISPR/Cas9 for gene knockout in alfalfa is still very challenging. Our initial single gRNA-CRISPR/Cas9 system had very low mutagenesis efficiency in alfalfa with no mutant phenotype. In order to develop an optimized genome editing system in alfalfa, we constructed multiplex gRNA-CRISPR/Cas9 vectors by a polycistronic tRNA-gRNA approach targeting the stay-green gene (MsSGR). The replacement of CaMV35S promoter by the Arabidopsis ubiquitin promoter to drive Cas9 expression led to a significant improvement in genome editing efficiency, whereas modification of the gRNA scaffold resulted in lower editing efficiency. The most effective multiplex system exhibited 75% genotypic mutagenesis efficiency, which is 30fold more efficient than the single gRNA vector. Importantly, phenotypic change was easily observed in the mutants, and the phenotypic mutation efficiency reached 68%. This highly efficient multiplex gRNA-CRISPR/Cas9 genome editing system allowed the generation of homozygous mutants with a complete knockout of the four allelic copies in the T0 generation. This optimized system offers an effective way of testing gene functions and overcomes a major barrier in the utilization of genome editing for alfalfa improvement.